Daily Use of Bilateral Custom‐Made Ankle‐Foot Orthoses for Fall Prevention in Older Adults: A Randomized Controlled Trial. Issue 8 (24th April 2019) - Wang, Changhong; Goel, Rahul; Zhang, Qianzi; Lepow, Brian; Najafi, Bijan
Abstract : OBJECTIVE: To examine the effects of bilateral custom‐made ankle‐foot orthoses (AFOs) to prevent falls for older adults with concern about or at risk for falling over 12‐month daily use. DESIGN: Secondary analysis of a randomized controlled trial. SETTING: Community‐dwelling older adults. INTERVENTION: Half of the participants were randomly allocated to an intervention group (IG) that received fitted walking shoes and bilateral custom‐made AFOs, and the other half were randomly allocated to a control group (CG) that only received fitted walking shoes. MEASUREMENTS: Self‐reported fall history of 12‐month duration was investigated at baseline and 12‐month follow‐up for both groups. Fall incidence rate and proportion of fallers were used as outcome measures to determine effects of 12‐month footwear intervention in either group. PARTICIPANTS: Adults aged 65 years and older with concern about or at risk for falling (n = 44). RESULTS: No significant between‐group differences in participant characteristics were observed at the baseline ( P = .144‐.882). Within the IG, significant reductions were found in the fall incidence rate ( P = .039) and the proportion of fallers ( P = .036) at the 12‐month follow‐up compared to the baseline. Within the CG, no significant change was found at the 12‐month follow‐up compared to the baseline for the fall incidence rate ( P = .217) or the proportion of fallers ( P = .757). When comparing the IG with the CG, there was no significant difference in the change from the baseline to the 12‐month follow‐up for the fall incidence rate ( P = .572) or the proportion of fallers ( P = .080). CONCLUSION: This study failed to demonstrate a significant benefit of bilateral custom‐made AFOs to reduce falls compared to fitted walking shoes. However, the AFO users had significant reductions in falls compared to the preceding year. A future study with a larger sample size is recommended to confirm these observations. CLINICAL TRIAL REGISTRATION —URL: http://www.clinicaltrials.gov . Unique identifier: NCT02819011. J Am Geriatr Soc 67:1656–1661, 2019